Pengaruh Pola Susunan Laminasi Terhadap Distribusi Tegangan Dan Regangan Tarik Pada Komposit CFRP Yang Berlubang - Alfian, Hamzah; Sudarsono, Sudarsono; Endriatno, Nanang (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2021)
The development of material technology is growing rapidly, especially in the manufacturing industry. One of the materials that are most often used and developed today is composite materials. The purpose of this study was to determine the effect of the pattern of laminate arrangement on the distribution of stress and tensile strain in perforated CFRP composites. The research method carried out is tensile testing using abaqus software, the specimen is designed with 8 laminates and the fiber direction is varied. The specimens were made with the ASTM D 5766 test standard and the properties used were carbon fiber composite type T800S/3900-2B. From the tensile test simulation results, it is found that the highest stress value in the composite with variations in fiber direction 0°, 45°, -45°, 90°, 90°, -45°, 45°, 0° the maximum stress value reaches 356.9 N/ mm², while the smallest stress occurs in the composite fiber direction 0°, 0°, 0°, 0°, 0°, 0°, 0°, 0° with the maximum stress value reaching 165.7 N/mm. The highest stress and strain that occurs in each specimen is located at the edge of the hole perpendicular to the direction of the force, the stress and strain increase based on variations in the direction of the fiber in the composite, the farther the orientation of the fiber direction to the direction of the applied force, the greater the stress concentration that occurs also.Keywords: Tensile test, CFRP composite, abaqus software